VD_FINDINFO HC / 2021 / 1050 vom 23. Dezember 2021 - VD Tribunal cantonal (2021)
EFFET SUSPENSIF, REJET DE LA DEMANDE, OBLIGATION D'ENTRETIEN, ENFANT, MINIMUM VITAL | 315 al. 4 let. b CPC (CH), 315 al. 5 CPC (CH)